Infection and the use of personal protective equipment among Primary Health Care workers during the COVID-19 pandemic - Jarbas da Silva Ziani; Jenifer Härter; Bruna Lixinski Zuge; Debora da Cruz Payão Pellegrini; Josefine Busanello; Karlo Henrique dos Santos Herrera (Universidade de São Paulo, 2024)
Abstract Objective: to analyze the frequency and associated risk factors for COVID-19 infection and the availability of Personal Protective Equipment used by primary healthcare workers. Method: a cross-sectional study was conducted over six months in Rio Grande do Sul. Descriptive analysis was performed, with the comparison of independent samples using Pearson's Chi-square test and Fisher's Exact test (p<.05). Results: the study included 206 (27%) healthcare workers who presented COVID-19 symptoms. There was a statistical association for the following variables: availability of surgical masks (p=.003), seeking information on the correct use of personal protective equipment (p=.045), having attended people with flu-like syndrome (p=.024), and believing that the highest risk of contamination is when attending a patient positive for coronavirus disease (p=.001). Conclusion: the availability of personal protective equipment is indispensable for COVID-19 prevention, with special emphasis on the use of surgical masks. Furthermore, the study highlighted the importance of providing Personal Protective Equipment in conjunction with guidance on its use.